Which Method of Assessing Depression and Anxiety Best Predicts Smoking Cessation: Screening Instruments or Self-Reported Conditions? - Watson, Noreen L (Nicotine Tob Res, 2020)
INTRODUCTION: Affective disorders and symptoms (ADS) are predictive of lower odds of quitting smoking. However, it is unknown which approach to assessing ADS best predicts cessation. This study compared a battery of ADS screening instruments with a single, self-report question on predicting cessation. Among those who self-reported ADS, we also examined if an additional question regarding whether participants believed the condition(s) might interfere with their ability to quit added predictive utility to the single-item question. METHODS: Participants (N = 2637) enrolled in a randomized controlled trial of web-based smoking treatments completed a battery of five ADS screening instruments and answered a single-item question about having ADS. Those with a positive self-report on the single-item question were also asked about their interference beliefs. The primary outcome was complete-case, self-reported 30-day point prevalence abstinence at 12 months. RESULTS: Both assessment approaches significantly predicted cessation. Screening positive for ≥ one ADS in the battery was associated with 23% lower odds of quitting than not screening positive for any (p = .023); those with a positive self-report on the single-item had 39% lower odds of quitting than self-reporting no mental health conditions (p < .001). Area under the receiver operating characteristic curve values for the two assessment approaches were similar (p = .136). Adding the interference belief question to the single-item assessment significantly increased the area under the receiver operating characteristic curve value (p = .042). CONCLUSIONS: The single-item question assessing ADS had as much predictive validity, and possibly more, than the battery of screening instruments for identifying participants at risk for failing to quit smoking. Adding a question about interference beliefs significantly increased the predictive utility of the single-item question. IMPLICATIONS: This is the first study to demonstrate that a single-item question assessing ADS has at least as much predictive validity, and possibly more, than a battery of validated screening instruments for identifying smokers at highest risk for cessation failure. This study also demonstrates adding a question about interference beliefs significantly adds to the predictive utility of a single, self-report question about mental health conditions. Findings from this study can be used to inform decisions regarding how to assess ADS in the context of tobacco treatment settings.